Editorial - Sánchez Cubides, Pedro Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Derecho y Realidad is the institutional journal of the Faculty of Law and Social Sciences of the Universidad Pedagógica y Tecnológica de Colombia, with biannual periodicity, which publishes original articles as a result of investigations in the social and legal field and in general, in the social and human sciences, in order to make them visible to the national and international community. For this reason, we are permanently inviting the academic and research community linked to these areas to present their research products for publishing in this magazine.